2018
DOI: 10.1101/432526
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene fitness landscape of group A streptococcus during necrotizing myositis

Abstract: 23[ABSTRACT] 24Necrotizing fasciitis and myositis are devastating infections characterized 25 by high mortality. Group A streptococcus (GAS) is a common cause of 26 these infections, but the molecular pathogenesis is poorly understood. We 27 report a genome-wide analysis using serotype M1 and M28 strains that 28 identified novel GAS genes contributing to necrotizing myositis in 29 nonhuman primates (NHP), a clinically relevant model. Using transposon 30 directed insertion-site sequencing (TraDIS) we identified… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 84 publications
(97 reference statements)
0
21
0
Order By: Relevance
“…60,100e102 Consistent with the data reported herein, transposon mutagenesis studies have shown rocA inactivation to significantly increase GAS fitness in mouse s.c. and NHP necrotizing myositis infection models. 60,101 The RNA-seq data demonstrate that rocA polymorphisms and rocA gene deletion significantly alter expression of many proven and putative virulence factors (Figure 3 and Supplemental Table S6). 43 As a result, rocA polymorphisms significantly increase M28 GAS virulence ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…60,100e102 Consistent with the data reported herein, transposon mutagenesis studies have shown rocA inactivation to significantly increase GAS fitness in mouse s.c. and NHP necrotizing myositis infection models. 60,101 The RNA-seq data demonstrate that rocA polymorphisms and rocA gene deletion significantly alter expression of many proven and putative virulence factors (Figure 3 and Supplemental Table S6). 43 As a result, rocA polymorphisms significantly increase M28 GAS virulence ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of a putative methionine transporter system (encoded by M28_Spy0263/0264/0265) and two putative export systems (encoded by M28_Spy0625/0626/0627 and M28_Spy1711/1712) results in decreased fitness in human saliva ex vivo and NHP muscle in vivo. 60,102 In addition, genes encoding several proven virulence factors regulated by RocA also contribute to GAS fitness in various anatomic niches ( Supplemental Table S8). 23,25,60,65,66,100e108 Furthermore, increased expression of nga and slo ( Figure 3 and Supplemental Table S8) was recently implicated in the emergence and global dissemination of epidemic serotype M1 and M89 GAS strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although genome-wide transposon mutagenesis has been employed to investigate GAS fitness genes ex vivo in saliva and blood samples, there are no data from samples from human or nonhuman primates (NHP) with myositis. Since group A streptococcal infections are relatively specific in their presentation in humans and NHP compared with other animal species, such as mice, Zhu and colleagues (14) took the excellent approach of collaborating with the Animal Health Trust (Sufffolk, United Kingdom) as well as with the Department of Veterinary Medicine, University of Cambridge (Cambridge, United Kingdom) to carry out these critical studies in the NHP cynomolgus macaques, which are similar to humans (Figure 1). Six animals were inoculated intramuscularly with the GAS strains M1 or M28, followed by necropsy and muscle biopsy after 28 hours.…”
Section: Virulence Gene Targetingmentioning
confidence: 99%